Dental fluorosis in the Vesuvius towns in AD 79: a multidisciplinary approach - Pierpaolo Petrone; Vincenzo Graziano; Chaturvedula Sastri; Thierry Sauvage; Marcello Mezzasalma; Mariano Paternoster; Fabio Maria Guarino (Taylor & Francis Group, 2019)
Background: Endemic fluorosis induced by high concentrations of fluoride in groundwater and soils is a major health problem in several countries, particularly in volcanic areas. Aim: To evaluate the occurrence of dental fluorosis resulting from exposure to high levels of environmental fluoride in 79 AD Herculaneum and close Vesuvius towns. Subjects and methods: The occurrence of dental fluorosis from teeth of the Herculaneum victims of the 79 AD eruption and some individuals from Pompeii (14-37 AD) and Nocera Inferiore (Salerno, IV sec. AD) was detected by means of Particle Induced Gamma-ray Emission technique (PIGE). Results: A clinical and analytical scenario of dental fluorosis resulted from the extreme high fluorine tooth content detected in teeth from Herculaneum and the Vesuvius area inhabitants. The adoption of PIGE technique has proved to be particularly effective in showing moderate as well as milder forms of dental fluorosis, otherwise not clearly detectable by clinical and histological analysis. Conclusions: Morphological, histological and elemental analysis of teeth of the 79 AD Herculaneum population show that in this area fluorosis occurred since Roman times.